2018
DOI: 10.1007/s00268-018-4552-7
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Hypoparathyroidism After Total Thyroidectomy in Children: Results from a National Registry

Abstract: IntroductionHypoparathyroidism is the most common complication following thyroidectomy. There are few population-based reports on the rate of hypoparathyroidism in children. The incidence of medical treatment of permanent hypoparathyroidism in children is reported using a national registry.MethodsThe study population included patients below 18 years of age undergoing total thyroidectomy reported to the Scandinavian Quality Registry for Thyroid, Parathyroid and Adrenal Surgery 2004–2014. Patients with previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 29 publications
(24 reference statements)
5
39
1
Order By: Relevance
“…In children and adolescents, complication rates were shown to be higher than in the adult population, with particularly high complication rates at young age < 6 years [35,36]. An analysis of the Swedish National Registry showed that for total thyroidectomy in children, the rate of permanent hypoparathyroidism reached 7.3% [37]. In the present analysis, median patient age was similar as in the aforementioned study.…”
Section: Discussionsupporting
confidence: 74%
“…In children and adolescents, complication rates were shown to be higher than in the adult population, with particularly high complication rates at young age < 6 years [35,36]. An analysis of the Swedish National Registry showed that for total thyroidectomy in children, the rate of permanent hypoparathyroidism reached 7.3% [37]. In the present analysis, median patient age was similar as in the aforementioned study.…”
Section: Discussionsupporting
confidence: 74%
“…In Denmark the overall prevalence of surgical hypoparathyroidism was 22 per 100,000 inhabitants [15]. In children undergoing neck surgery, the incidence of hypoparathyroidism after neck surgery can be as high as 7.3%, even if the operation has been performed in endocrine surgery referral centers [75].…”
Section: Post Surgical Hypoparathyroidismmentioning
confidence: 99%
“…Table 1 also shows in which studies thyroidectomies were performed by a high-volume or a low-volume surgeon. Eight studies reported that the thyroidectomy was performed by a high-volume surgeon [10, 11, 13-15, 21, 29, 31]. In the study by Cohen et al [23], surgery was performed by a low-volume surgeon.…”
Section: Resultsmentioning
confidence: 99%
“…Sugino et al [26] reported all patients to be euthyroid at the time of surgery, without reporting the used preoperative treatment protocol. The other included studies did not report on preoperative preparation or preoperative thyroid hormone levels in their patients [10, 13, 15, 17-22, 24, 25, 28-31]. Further characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation